BANTUAN MESIN PEMBUATAN TERASI UNTUK PENGUSAHA UMKM DI DESA PULAU KAMPAI KECAMATAN PANGKALAN SUSU KABUPATEN LANGKAT - Luthfi Parinduri; Abdul Haris Nasution; Muksin R. Harahap; Bonar Harahap; Ahmad Bakhori; Mahrani Arfah; Satria Yudha Prayogi (Jurnal Pengabdian Mitra Masyarakat, 2022)
Economic growth in Indonesia is influenced by various factors, one of which is the involvement of UMKM. In accordance with the 1945 Constitution article 33 paragraph 4, UMKM are part of the national economy with an independent perspective and have great potential to improve people's welfare. The parties responsible for developing and fostering UMKM are the Government, Business Entities and the community, including Universities. Empowerment of UMKM through the provision of mentoring facilities and strengthening assistance aims to grow and improve the capabilities and competitiveness of these UMKM. One of the Terasi entrepreneurs in Pulau Kampai Village who has been producing terasi for more than 10 years, has marketed his products to various regions in North Sumatra and Aceh as well as other areas. The large demand for terasi  produced makes it unable to supply. This is because the existing machines are used today are small capacity. Therefore, the UISU Faculty of Engineering has provided assistance in the form of terasi processing machine with a larger capacity. It is hoped that with the use of this assistance machine, its production capacity will increase while at the same time being able to meet the ever-increasing demand.